Association of Antimicrobial Susceptibility and Treatment Outcome in Acne Vulgaris Patients: A Pilot Study - Yadav, Ashvini K.; Bhooshan, Suneel; Johnson, Allen; Asati, Dinesh P.; Nema, Shashwati; Biswas, Debasis (Journal of Laboratory Physicians, 2020)
Purpose Cutibacterium acnes (C. acnes) is an emerging pathogen that is highly resistant to antibiotics and is capable of causing persistent infections that are difficult to treat.Methods & Materials Acne vulgaris patients visiting dermatology OPD of our tertiary care hospital during the study period of 2 months were recruited. Skin swabs were collected, and the sample was processed on 5% sheep-blood agar for anaerobic culture by the GasPak method. Isolates were identified by the standard biochemical test. Antimicrobial susceptibility testing was performed for clinically relevant antibiotics by the E-strip method. The clinical response was evaluated after 1-month follow-up to the prescribed antibiotics.Results Minocycline, doxycycline, ceftriaxone, and tetracycline were the most effective antibiotics. Nonsusceptibility to clindamycin and erythromycin were observed in 11.9% and 31% isolates, respectively, with 9.5% isolates being nonsusceptible to both. For none of the antibiotics we found significant difference in the proportion of susceptible and nonsusceptible isolates between mild, moderate, and severe grades of acne vulgaris. For none of the antibiotic regimens, significant difference was observed between nonresponders and responders. Twenty-seven patients received clindamycin and among them 16 of 19 responders and 6 of 8 nonresponders yielded growth of clindamycin-susceptible isolates (p = 0.57).Conclusion We observed significant prevalence of resistant strains of C. acnes among patients with acne vulgaris. No association was observed between in vitro susceptibility results and treatment outcome.
Keywords: Cutibacterium acnes; Acne vulgaris; Antibigram; In vitro susceptibility; Propionibacterium acnes